Elemental composition of vaping and smoking aerosols: Influence of liquid type and tank conditions - Joanna Chwał; Anna Filipowska; Magdalena Antonowicz; Dawid Lisicki; Paweł Kostka; Rafał Doniec (PLoS ONE, 2025)
This study compares the elemental composition of aerosols produced by e-cigarettes and traditional cigarettes using Energy Dispersive Spectroscopy (EDS). Both homemade and store-bought e-liquids were tested under various tank conditions (full, half, and empty), and emissions were collected using nitrocellulose membranes and coil cotton. Additional measurements were performed on unheated e-liquids, cigarette filters, unused cotton, and membranes to assess background contamination. Key elements identified included chromium (Cr), aluminum (Al), sodium (Na), sulfur (S), chlorine (Cl), and copper (Cu). Homemade e-liquids showed significantly higher Cr and Al concentrations, especially under partial tank conditions, suggesting intensified coil degradation. Store-bought e-liquids demonstrated more stable emission profiles. Traditional cigarette smoke contained fewer trace metals but exhibited different elemental patterns. Supplementary viscosity and thermal analyses revealed that homemade liquids degrade more rapidly under heat, which may enhance metal leaching from coils. These findings underscore the influence of liquid composition and device conditions on emission profiles, emphasizing the need for quality control in e-liquid production and further toxicological evaluation of e-cigarette use.